1987 annual meeting of the Boards of Governors : summary proceedings - International Bank for Reconstruction and Development; International Finance Corporation; International Development Association (Washington D.C. World Bank, 1987)
The 1987 Annual Meeting of the Board of Governors of the International Bank for Reconstruction and Development, held jointly with that of the International Monetary Fund, took place in Washington DC. The summary proceedings record, in alphabetical order member countries, the texts of statements of the Governors relating to the activities of the Bank, IFC and IDA.
osc 11/4/17
Ref
Keywords: World Bank; International Bank for Reconstruction and Development; International Finance Corporation; International Development Association